Doxorubicin-Immersed Skeletal Muscle Grafts Promote Peripheral Nerve Regeneration Across a 10-mm Defect in the Rat Sciatic Nerve - Takeuchi, Hisataka; Sakamoto, Akio; Ikeguchi, Ryosuke; Ota, Soichi; Oda, Hiroki; Yurie, Hirofumi; Mitsuzawa, Sadaki; Matsuda, Shuichi (Journal of Reconstructive Microsurgery, 2020)
Background The treatment of peripheral nerve defects requires bridging materials. Skeletal muscle grafts have been studied as an alternative to nerve autografts because they contain longitudinally aligned basal laminar tubes that are similar to axons. Several pretreatment methods for muscle grafts have promoted axonal regeneration. Here, a new method of doxorubicin pretreatment was used, and the efficacy of the pretreated muscle graft was evaluated in a rat model of a sciatic nerve defect.Methods A rat model of a 10-mm sciatic nerve defect was analyzed in three settings: muscle grafts with and without doxorubicin pretreatment (M-graft-w-Dox and M-graft-w/o-Dox groups, respectively) and a nerve autograft group (N-graft) (n = 6/group). The M-graft-w-Dox group was immersed in a doxorubicin solution for 10 minutes and rinsed with saline. Analyses of target muscle atrophy, electrophysiology, and histology were performed 8 weeks after grafting.Results Electrophysiological parameters and target muscle atrophy were significantly superior in the M-graft-w-Dox group compared with the M-graft-w/o-Dox group. Histological assessment revealed the presence of a significantly greater number of regenerated axons in the M-graft-w-Dox group versus the M-graft-w/o-Dox group, while there were no significant differences between the M-graft-w-Dox and N-graft groups. The diameter of myelinated axons of the regenerated nerve in the M-graft-w-Dox group was significantly larger than that in the M-graft-w/o-Dox group, while it was not significantly different compared with the N-graft group.Conclusion Pretreatment of muscle grafts with doxorubicin promoted significant peripheral nerve regeneration. This method may represent a new option for the treatment of peripheral nerve defects.
Keywords: peripheral nerve; doxorubicin; pretreatment; muscle; graft; nerve regeneration